Counseling for Prenatal Congenital Heart Disease-Recommendations Based on Empirical Assessment of Counseling Success - Alexander Kovacevic; Andreas Simmelbauer; Sebastian Starystach; Michael Elsässer; Andreas Müller; Stefan Bär; Matthias Gorenflo (Frontiers Media S.A., 2020)
Objectives: Empirical assessment of parental needs and affecting factors for counseling success after prenatal diagnosis of congenital heart disease (CHD).Methods:Counseling success after fetal diagnosis of CHD was assessed by a validated standardized questionnaire. The dependent variable "Effective Counseling" was measured in five created analytical dimensions (1. "Transfer of Medical Knowledge-ToMK"; 2. "Trust in Medical Staff-TiMS"; 3. "Transparency Regarding the Treatment Process-TrtTP"; 4. "Coping Resources-CR"; 5. "Perceived Situational Control-PSC"). Analyses were conducted with regard to influencing factors and correlations.Results: Sixty-one individuals (n = 40 females, n = 21 males) were interviewed in a tertiary medical care center. Median gestational age at first parental counseling was 28 + 6 weeks. Parental counseling was performed four times (median), mostly by pediatric cardiologists (83.6%). Overall counseling was successful in 46.3%, satisfying in 51.9%, and unsuccessful in 1.9%. Analyses of the analytical dimensions show that counseling was less successful for TOMK (38.3%) and PSC (39%); success rates were higher if additional written information or links to web sources were provided (60 and 70%, respectively). Length of consultation was positively correlated to counseling success for ToMK (r = 0.458), TrtTP (r = 0.636), PSC (r = 0.341), and TiMS (r = 0.501). Interruptions were negatively correlated to the dimensions TiMS (r = −0.263), and TrtTP (r = −0.210). In the presence of high-risk CHD (37.5%) overall counseling success was lower (26.1%). By cross table analysis and to a low degree of positive correlation in one dimension (ToMK; r = 0.202), counseling tends to be less successful for ToMK, TrtTP, and TiMS if parents have not been counseled by cardiologists. Analyses regarding premises show a parental need for a separate counseling room, which significantly impacts ToMK (r = −0,390) and overall counseling success (r = −0.333). A language barrier was associated with lower success rates for ToMK, TiMS, and CR (21.4, 42.9, and 30.8%).Conclusions: Data from this multidisciplinary study indicate that parents after fetal diagnosis of CHD need uninterrupted counseling of adequate duration and quality in a separate counseling room. Providing additional written information or links to adequate web sources after initial counseling seems necessary. High-risk CHD needs more attention for counseling. There is a trend towards more counseling success if provided by cardiologists.